2020
DOI: 10.1002/ece3.6231
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of migratory fish: Implications for conservation and stocking programs

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(63 reference statements)
0
4
0
1
Order By: Relevance
“…The Três Marias reservoir appears to act as a barrier to the more significant movements of P. costatus individuals, probably because it is a novel habitat lacking the environmental and hydraulic cues required to guide translocated individuals to river stretches that are more suitable for spawning and recruitment. Moreover,Pimentel et al (2020) found little genetic exchange among P. costatus populations that inhabit different tributaries of the Três Marias reservoir, reinforcing the notion that large reservoirs may act as a barrier to the more significant movements of migratory fish species.…”
mentioning
confidence: 70%
“…The Três Marias reservoir appears to act as a barrier to the more significant movements of P. costatus individuals, probably because it is a novel habitat lacking the environmental and hydraulic cues required to guide translocated individuals to river stretches that are more suitable for spawning and recruitment. Moreover,Pimentel et al (2020) found little genetic exchange among P. costatus populations that inhabit different tributaries of the Três Marias reservoir, reinforcing the notion that large reservoirs may act as a barrier to the more significant movements of migratory fish species.…”
mentioning
confidence: 70%
“…Besides, the genetic methods have been also used to estimate the migration and gene flow (Almada et al 2017 ; Castilho, Cunha, Faria, Velasco, & Robalo, 2017 ), improving our understanding about the demography and evolution life‐history studies of migratory fish populations (Mattingsdal et al, 2019 ; Pavlova et al, 2017 ). Especially in cases that there were habitat loss and fragmentation of riverbeds that influence not only the behavior but also the population dynamics ( Pimentel & Ludwig, in press ), thus, the genetics have been complementary implemented to ecological knowledge (Piorski et al, 2008 ; Savary et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic structure of the population of P. costatus in the São Francisco River basin has been recently investigated ( Pimentel et al, in press ). However, the life history and the interactions and feedback between the environmental stochastic events and evolutionary mechanisms (herein threatened as eco‐evolutionary processes; i.e., Pelletier, Garant, & Hendry, 2009 ) that have shaped the current pattern population structure have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…É importante considerar que a transposição também pode resultar na quebra de barreiras físicas naturais presentes na bacia do Rio São Francisco, o que poderia impactar negativamente a diversidade genética, estrutura populacional e, principalmente, o fluxo gênico (migração) (e.g. PIMENTEL et al, 2020).…”
Section: Indroduçãounclassified